An Experiment Design for Determining the Volume of Traditional Eucalyptus Oil with Variations in Fluid Flow Speed - Siregar, Nur Hamida; Toifur, Moh.; Pramudya, Yudhiakto (Indonesian Review of Physics (IRiP), 2019)
This study aimed to determine the volume of traditional eucalyptus oil from distillation with variations in fluid flow velocity. The method of distillation was distillation with water (water distillation). The material was eucalyptus leaves. To determine the volume of eucalyptus oil produced by distillation, the distillation device was set at the height of the condenser to the source of flow fluid, which was at an altitude of 15 cm, 25 cm, 35 cm, 45 cm, and 55 cm. Variation in the height of the condenser would affect the fluid flow rate. The faster the fluid flow rate, the greater the convection coefficient so that it increased the heat transfer rate. This results in greater volume (capacity) of oil produced. From these experimental results, most volumes of eucalyptus oil obtained from the distillation was obtained at 55 cm of the height of condenser with 3.6 mLof oil volume.